2000
DOI: 10.1021/es991334v
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Speciation in Sediments Affected by Dumped Mining Residues in the Drainage Area of the Idrija Mercury Mine, Slovenia

Abstract: Mercury (Hg) concentrations and Hg phases were investigated in contaminated sediments and flooded soils in the drainage area of the Idrija Hg mine, Slovenia. The main aim of this study was the analytical separation and quantification of cinnabar (HgS) and noncinnabar Hg compounds in sediments contaminated by mining residues. Separation of Hg phases was performed by means of a solid-phase-Hg-thermo-desorption technique complemented by selective extraction of organically bound Hg. Speciation measurements indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(107 citation statements)
references
References 12 publications
7
98
0
2
Order By: Relevance
“…Thus, we assume that most Hg present in the calcine material is bound to mineral components mainly by iron oxides, which were formed when the cinnabar-bearing ore was being roasted. Earlier studies already suggested that Hg 0 formed during thermal breakdown of cinnabar is re-condensed during cooling of the material and adsorbed to iron oxide surfaces (Biester et al 2000). In addition to matrix-bound Hg, some calcine samples contained traces of cinnabar.…”
Section: F I G U R E 3 T O T a L Me T A L C O N C E N T R A T I O Nmentioning
confidence: 96%
“…Thus, we assume that most Hg present in the calcine material is bound to mineral components mainly by iron oxides, which were formed when the cinnabar-bearing ore was being roasted. Earlier studies already suggested that Hg 0 formed during thermal breakdown of cinnabar is re-condensed during cooling of the material and adsorbed to iron oxide surfaces (Biester et al 2000). In addition to matrix-bound Hg, some calcine samples contained traces of cinnabar.…”
Section: F I G U R E 3 T O T a L Me T A L C O N C E N T R A T I O Nmentioning
confidence: 96%
“…The next Hg compounds to decompose are the mercury sulphides between 170 and 330ºC. As noted by Lopez-Anton et al [22], there are two different HgS crystalline structures: cubic black HgS or metacinnabar which decomposes at 265ºC and trigonal red HgS or cinnabar which decomposes at 290ºC [22,24]. HgO and HgSO 4 decompose at higher temperatures than mercury sulphides.…”
Section: Thermal Decomposition Of Mercury Pure Compounds In a Matrix mentioning
confidence: 96%
“…HgCl 2 <HgS<HgO<HgSO 4 ) according to the temperature of desorption [22]. Thermal decomposition has been used to identify Hg compounds in soil contaminates, sediment samples, iron-based sorbents [23][24][25], and even in mercury lamp wastes [26]. However, there is a lack of a similar knowledge concerning the speciation of Hg in coal combustion products [27].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos anteriores, com um sistema de termodessorção acoplado a um espectrômetro de absorção atômica, mostraram que diferentes espécies de mercúrio são liberadas da matriz, por aquecimento, a diferentes faixas de temperatura [14][15][16][24][25][26][27] . Nas mesmas condições A Figura 5 mostra termogramas representativos de todas as amostras analisadas, provenientes dos diferentes locais de amostragem.…”
Section: Especiação De Mercúrio Por Tdaasunclassified
“…Algumas amostras apresentaram ombros ao lado do pico principal, indicando a presença de mais de um tipo de ligação de Hg na matriz. Esse tipo de perfil já foi observado em outros trabalhos 15,26 e foi atribuído a complexos organominerais.…”
Section: Agradecimentosunclassified